2011
DOI: 10.1063/1.3593958
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxially grown semiconducting hexagonal boron nitride as a deep ultraviolet photonic material

Abstract: Hexagonal boron nitride (hBN) has emerged as an important material for various device applications and as a template for graphene electronics. Low-dimensional hBN is expected to possess rich physical properties, similar to graphene. The synthesis of wafer-scale semiconducting hBN epitaxial layers with high crystalline quality and electrical conductivity control has not been achieved but is highly desirable. Large area hBN epitaxial layers (up to 2 in. in diameter) were synthesized by metal organic chemical vap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
162
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(176 citation statements)
references
References 17 publications
3
162
1
Order By: Relevance
“…Carbon to boron (C:B) ratio is varied from ∼8 to 80 for a C 3 H 8 flow rate from 0.5 sccm to 5 sccm. Figure 2(a) shows a representative X-ray diffraction (XRD) θ -2θ scan of a h-(BN) 1-x (C 2 ) x sample with x = 0.032 revealing a lattice constant of c = 6.70 Å, which closely matches with a value of c = 6.67 Å for hexagonal BN (h-BN) epilayers grown at the same temperature 15,16 and also with that of graphite ( Fig. 1(a)).…”
Section: Methodssupporting
confidence: 56%
“…Carbon to boron (C:B) ratio is varied from ∼8 to 80 for a C 3 H 8 flow rate from 0.5 sccm to 5 sccm. Figure 2(a) shows a representative X-ray diffraction (XRD) θ -2θ scan of a h-(BN) 1-x (C 2 ) x sample with x = 0.032 revealing a lattice constant of c = 6.70 Å, which closely matches with a value of c = 6.67 Å for hexagonal BN (h-BN) epilayers grown at the same temperature 15,16 and also with that of graphite ( Fig. 1(a)).…”
Section: Methodssupporting
confidence: 56%
“…[7][8][9][10] Epitaxial h-BN layers with high optical qualities can be achieved, 7,20 but these materials generally lack the intrinsic FX transitions above 5.7 eV due to the presence of native and point defects. 7,20 Most recent studies have suggested that the D-series emission lines are due to the recombination of excitons bound to deep acceptors formed by carbon impurities occupying the nitrogen sites, and h-BN epilayers exhibiting pure intrinsic FX emission can be obtained by growing the materials under high ammonia flow rates. 21 However, the detailed features of the FX transitions in h-BN epilayers are distinctly different from those in h-BN bulk crystals, 21 which is what remains to be investigated and understood.…”
mentioning
confidence: 99%
“…With an energy bandgap around 6.5 eV, h-BN is emerging as an important semiconductor material. [3][4][5][6][7] With its unique physical properties including high temperature and chemical stability, h-BN has potential applications in high temperature/power electronic device applications. P-type conductivity seems to be more easy to realize in h-BN than in AlN, which reveals the potential of h-BN for deep UV emitter and detector applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Different forms of physical vapor deposition (PVD), such as pulsed laser deposition, 23 and reactive magnetron sputtering, 24 have also been used for h-BN thin film growth. While these studies exhibit the progress being made in h-BN growth, a single scalable synthesis method which combines highcrystalline quality with absolute thickness control remains elusive.…”
mentioning
confidence: 99%